The impact of investment on drinking water quality in rural China. Issue 2 (2nd May 2017) - Yue, Ai; Shi, Yaojiang; Luo, Renfu; Zhang, Linxiu; Johnson, Natalie; Rozelle, Scott; Zhao, Qiran
Abstract : Purpose: Although access to safe drinking water is one of the most important health-related infrastructure programs in the world, drinking water remains a large problem in China today, especially in rural areas. Despite increased government investment in water resource protection and management, there is still an absence of academic studies that are able to document what path the investment has taken and whether it has had any tangible impact. The purpose of this paper is to analyze the impact of drinking water investment on drinking water in China. Design/methodology/approach: The authors make use of nationally representative data from 2005 and 2012 to measure the impact of drinking water investment among 2, 028 rural households in 101 villages across five provinces. Both ordinary least squares regression and probit regression are used to analyze the correlates and the impact of drinking water investment. Findings: The authors demonstrate that water quality was likely a significant problem in 2004 but that China's investment into drinking water appears to have resulted in initial improvements during the study period. The authors show that the most significant change came about in terms of hardware: villages that received more drinking water investment now have more piped tap water and more access to water treatment infrastructure (disinfecting and filtering facilities). High rates of rural resident satisfaction with drinking water suggest the effects of drinking water investment are being felt at the village level. Originality/value: To the authors' knowledge, this is the first empirical study on drinking water investment over time in rural China using nationally representative data.